Values shift in response to social learning through deliberation about protected areas. (January 2023) - Andrade, Riley; van Riper, Carena J.; Goodson, Devin J.; Johnson, Dana N.; Stewart, William; López-Rodríguez, María D.; Cebrián-Piqueras, Miguel A.; Horcea-Milcu, Andra Ioana; Lo, Veronica; Raymond, Christopher M.
Highlights: This longitudinal, mixed methods study empirically measured learning and values. Relational learning activated values through an increased understanding of others. Social values of protected areas changed in response learning through deliberation. Multi-level values changed to different degrees based on psychological stability. Value shifts required learning situated within broader communities of practice. Abstract: Salient, long-term solutions to address global environmental change hinge on management strategies that are inclusive of local voices and that recognize the array of values held by surrounding communities. Group-based participatory processes that involve deliberation of multiple stakeholders with varying perspectives—particularly social learning—hold promise to advance inclusive conservation by identifying and creating a shared understanding of the landscape. However, few studies have empirically investigated how the value basis of stakeholder deliberation changes over time in relation to social learning. This study provided a novel platform for local stakeholders from Interior Alaska to deliberate on landscape change and associated management practices in ways that shifted their value orientations. In particular, we used a pre-test, post-test experimental design involving mixed methods to measure how different types of values changed as a result of social learning through an online discussion forum. We found evidence that social learning: 1) activated shared values that were previously hidden through building a relational understanding of others, and 2) shifted values that spanned three levels of psychological stability. As hypothesized, social values that represented expressed preferences for landscape change were most likely to shift in association with social learning. Conversely, shifts in individual values towards self-transcendence required learning to go beyond the discussion forum and be situated within the participants' broader communities of practice. Overall, this longitudinal study highlights how social learning facilitated through deliberation presents opportunities to identify shared values and spark value shifts across stakeholder groups, thus incorporating diverse viewpoints into decision-making about global environmental change.